(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Analysis of the prerroman place-names of Tartessian origin in the SW of Iberia. The recent publication of the tartessian cemetery of Conis- turgis Medellín (Badajoz), proves a tartessian colonization documented by place-names, archaeological materials, “SW inscriptions” or “tartessian in- scriptions” and “tartessian” personal names. This colonial expansion took place in the peripherical areas all over the southwest of the Iberian Peninsula, from a nuclear area in the Guadalquivir valley along the Atlantic cost of Portugal up to Gallaecia and inlands in the Guadiana valley as far as the Tagus river.